Gallic Acid Inhibits Bladder Cancer T24 Cell Progression Through Mitochondrial Dysfunction and PI3K/Akt/NF-κB Signaling Suppression - Zeng, Maolin; Su, Yang; Li, Kuangyu; Jin, Dan; Li, Qiaoling; Li, Yan; Zhou, Benhong (Frontiers in Pharmacology, 2020)
Gallic acid (GA), a hydrolyzable tannin, has a wide range of pharmacological activities. This study revealed that, GA significantly inhibited T24 cells viability in a concentration- and time- dependent manner. The IC50 of GA stimulating T24 cells for 24, 48, and 72 h were 21.73, 18.62, and 11.59 µg/ml respectively, and the inhibition rate was significantly higher than the positive control drug selected for CCK-8 assay. Meanwhile, after GA treatment, the morphology of T24 cells were changed significantly. Moreover, GA significantly inhibited T24 cells proliferation and blocked T24 cells cycle in S phase (p < 0.001). GA induced T24 cells apoptosis (p < 0.001), accompanied by reactive oxygen species (ROS) accumulation and mitochondrial membrane potential (MMP) depolarization. Western blotting analysis showed that GA significantly increased Cleaved caspase-3, Bax, P53, and Cytochrome C (Cyt-c) proteins expression, and decreased Bcl-2, P-PI3K, P-Akt, P-IκBα, P-IKKα, and P-NF-κB p65 proteins expression in T24 cells (p < 0.05). Real-Time PCR results verified that GA significantly promoted Caspase-3, Bax, P53, and Cyt-c genes expression, and inhibited Bcl-2, PI3K, Akt, and NF-κB p65 genes expression (p < 0.001). However, on the basis of GA (IC50) stimulation, NAC (an oxidative stress inhibitor) pretreatment reversed the apoptotic rate of T24 cells and the expression of Bax, Cleaved caspase-3, P53, Bcl-2 proteins, and the MMP level in T24 cells, as well as the expression of Cyt-c protein in T24 cells mitochondria and cytoplasm. In addition, GA significantly suppressed T24 cells migration and invasion ability with VEGF protein inhibition (p < 0.001). Briefly, GA can inhibit T24 cells proliferation, metastasis and promote apoptosis, and the pro-apoptotic activity is closely associated with mitochondrial dysfunction and PI3K/Akt/NF-κB signaling suppression. Our study will help in finding a safe and effective treatment for bladder cancer.